Chekhov and Shakespeare: Motif of the Theater in the dramatic Plot of "The Tempest" and "The Seagull" - Никипелова, Нина Александровна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The last play Shakespeare’s "The Tempest" (1611) and Chekhov’s "The Seagull" (1896) share almost three centuries. The motif of the theater, "the power of the theater", in the plots of these dramatic works - no matter how different their poetics - can serve as a bridge between authors and epochs. The action in the both plays happen in the "natural" sceneries. And the deck of the ship in the storm, and the magical island, and the beach of the "witch’s" lake becomes the scene. "The Tempest" begins by the threat of the death that is averted by the good will, in "The Seagull" event ends the death of the hero, has not averted by those who could and should have done it.